The role of the beta-Mg17Al12 phase on the anomalous hydrogen evolution and anodic dissolution of AZ magnesium alloys. (1st April 2020) - Ubeda, C.; Garces, G.; Adeva, P.; Llorente, I.; Frankel, G.S.; Fajardo, S.
Highlights: Anomalous HE observed for AZ31 and AZ91 Mg alloys. Passivity exhibited by Mg17 Al12 with anomalous HE originating at anodic regions. Mg17 Al12 phase exhibited lower HE rates than AZ Mg alloys during polarization. Results consistent with anomalous HE originating at actively dissolving Mg sites. Greater amounts of Mg17 Al12 decrease dissolution rates of Mg matrix. Abstract: The role of the Mg17 Al12 second phase on the anomalous HE and anodic dissolution of AZ31 and AZ91 Mg alloys was investigated. A passive-like behavior was exhibited by the Mg17 Al12 phase with strong anomalous HE originating from local anodic regions where the passive film had broken down. The Mg17 Al12 exhibited lower HE rates than the AZ Mg alloys during anodic polarization. Surface characterization confirmed that dissolution of Mg17 Al12 in the AZ91 alloy only occurred above the Eb for the Mg17 Al12 . Under anodic polarization, greater amounts of Mg17 Al12 are beneficial for AZ Mg alloys durability, decreasing the Mg matrix dissolution rates.